Answer:
x² + 2x + 3
Explanation:
given
![(x^3+3x^2+5x+3)/(x+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tsxu3xlc8ozebpw73u11kgdx5udy3xgt38.png)
One way of dividing is to use the divisor as a factor in the numerator
Consider the numerator
x²(x + 1) - x² + 3x² + 5x + 3
= x²(x + 1) + 2x(x + 1) - 2x + 5x + 3
= x²(x + 1) + 2x(x + 1) + 3(x + 1) - 3 + 3
= x²(x + 1) + 2x(x + 1) + 3(x + 1) + 0
![(x^3+3x^2+5x+3)/(x+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tsxu3xlc8ozebpw73u11kgdx5udy3xgt38.png)
=
= x² + 2x + 3 ← quotient